2022
DOI: 10.1063/5.0079857
|View full text |Cite|
|
Sign up to set email alerts
|

Reducing solid conduction in electrothermally driven MEMS Pirani gauge using integrated polymeric thin film

Abstract: An electrothermally driven MEMS Pirani gauge with an integrated polymeric (SU-8) thin film is proposed. The structured architecture utilizes the miniaturization advantage of microbridge-type Pirani gauges while combining the lower conduction losses of membrane-based gauges. The integrated polymeric film is highly effective in providing mechanical strength to the metallic resistor and in reducing solid conduction loss to the substrate. Consequently, the dynamic range is extended, and the proposed device shows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Since its invention, the quest for wider dynamic range, power efficiency, and improved sensitivity has been active [8][9][10][11][12][13][14][15]. Different approaches based on structural and dimensional optimizations were proposed for improving the gauge performance [9]. The lower vacuum detection limit of a typical Pirani gauge depends on the ratio of gaseous conduction to solid conduction [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since its invention, the quest for wider dynamic range, power efficiency, and improved sensitivity has been active [8][9][10][11][12][13][14][15]. Different approaches based on structural and dimensional optimizations were proposed for improving the gauge performance [9]. The lower vacuum detection limit of a typical Pirani gauge depends on the ratio of gaseous conduction to solid conduction [10].…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, miniaturization of Pirani sensors is of significance. In recent decades, the development of MEMS technology has greatly promoted the miniaturization of traditional sensors [30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The miniaturized Pirani sensors, also known as the MEMS Pirani sensors, can not only reduce the weight and size of the devices, but also can cut down power consumption and production costs [44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Garg et al proposed an electrothermally actuated Micro-Electro-Mechanical System (MEMS, Micro-Electro-Mechanical System) Pirani meter with an integrated polymer film. Experimental results showed that the integrated polymer film was very effective in providing mechanical strength to metal resistors and reducing solid conduction losses to the substrate [10]. Li et al believed that due to the development of smart devices, embedded and ubiquitous communication technologies, and the combination with the online world, film media operations had become more important to the real world.…”
Section: Introductionmentioning
confidence: 99%